1998
DOI: 10.1074/jbc.273.18.11313
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Regulation of Neutral Sphingomyelinase in Tumor Necrosis Factor-α-induced Cell Death

Abstract: Tumor necrosis factor-␣ (TNF␣)-induced cell death involves a diverse array of mediators and regulators including proteases, reactive oxygen species, the sphingolipid ceramide, and Bcl-2. It is not known, however, if and how these components are connected. We have previously reported that GSH inhibits, in vitro, the neutral magnesium-dependent sphingomyelinase (N-SMase) from Molt-4 leukemia cells. In this study, GSH was found to reversibly inhibit the N-SMase from human mammary carcinoma MCF7 cells. Treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
255
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 332 publications
(271 citation statements)
references
References 64 publications
15
255
0
Order By: Relevance
“…These investigators showed that physiologic concentrations of glutathione, which neutralizes free radicals, inhibits NSMase (Liu and Hannun, 1997). A depletion in glutathione, which occurs during oxidative stress, may result in NSMase activation (Liu et al, 1998). During TNF-mediated cell death glutathione depletion is progressive, and NSMase activation and ceramide generation occur after 6 ± 12 h. This contrasts with the rapid ceramide generation that occurs in response to environmental stress in some cells (Figure 1), an event likely mediated via ASMase.…”
Section: Mechanisms Of Ceramide Generationmentioning
confidence: 99%
“…These investigators showed that physiologic concentrations of glutathione, which neutralizes free radicals, inhibits NSMase (Liu and Hannun, 1997). A depletion in glutathione, which occurs during oxidative stress, may result in NSMase activation (Liu et al, 1998). During TNF-mediated cell death glutathione depletion is progressive, and NSMase activation and ceramide generation occur after 6 ± 12 h. This contrasts with the rapid ceramide generation that occurs in response to environmental stress in some cells (Figure 1), an event likely mediated via ASMase.…”
Section: Mechanisms Of Ceramide Generationmentioning
confidence: 99%
“…Downregulation of VEGF and its receptor may be associated with apoptosis, which may be linked in the pathogenesis of inflammatory lung diseases such as emphysema and COPD. GSH and other thiols such as NAC inhibit TNFa-induced sphingomyelin hydrolysis, ceramide generation and programmed cell death (apoptosis), suggesting that GSH has antiapoptotic properties through its ability to detoxify oxidants and free radicals [214].…”
Section: Against Inflammatory Events In Lungsmentioning
confidence: 99%
“…TNF-α initiates the pathway through TNFR1 (55-kDa receptor) leading to phospholipase A2 activation, generation of arachidonic acid, and subsequent activation of SMase [27]. TNF-α-stimulated cells are redox-sensitive [28]. Some studies showed that ROS participate in TNF-α-mediated ceramide formation, suggesting that the ROS-sensitive pathway may be located upstream of ceramide formation [29].…”
Section: Tumor Necrosis Factor-α and Ceramidementioning
confidence: 99%